ANALISIS GERAKAN LITERASI SEKOLAH TERHADAP MINAT BACA PESERTA DIDIK KELAS V DI SD PENGGERAK PURWAKARTA - Shanty Sulistyaningrum, - (2023)
The School Literacy Movement is an activity program from the government that aims to foster and develop students' interest in reading, especially in elementary schools. In each activity there are driving and inhibiting factors that aim to describe and know the implementation of the School Literacy Movement, driving and inhibiting factors, and efforts to overcome the inhibiting factors in the School Literacy Movement on students' reading interest. The location of the research is at SD Negeri 1 Nagrikidul and the target of implementing the School Literacy Movement for all school parties while the target of reading interest is for fifth grade students. The data collection techniques in this study are observation, interviews, questionnaires, and documentation. The results of the research of the School Literacy Movement at SD Negeri 1 Nagrikidul have been in the learning stage. Supporting factors consist of the active role of all school parties, educators supervising literacy learning activities, a reading-friendly environment, all school parties producing written works, and support for the implementation of the School Literacy Movement at SD Negeri 1 Nagrikidul. The inhibiting factors are educators who are less effective in implementing literacy learning, facilities and infrastructure are less comfortable such as libraries are not well organized and reading books in the literacy corner are also incomplete, and there is no special day in reading activities. Efforts to overcome this are all schools holding meetings regarding the plans of the School Literacy Movement in the future, improving the administration of library management, adding or updating reading books to attract the attention of students to read. Based on the results of research data analysis that students' reading interest currently has a high category. Therefore, the implementation of the School Literacy Movement in the future remains consistent and has a plan for the School Literacy Movement program to run more conducively. Keywords: Analysis of the School Literacy Movement, Reading Interest Elementary school of education